Anti-cancer effects of targeting Hsp70 in tumor stromal cells - Gabai, Vladimir L. (Cancer Res, 2016)
The stress-induced chaperone protein Hsp70 enables the initiation and progression of many cancers, making it an appealing therapeutic target for development. Here we show that cancer cells resistant to Hsp70 inhibitors in vitro remain sensitive to them in vivo, revealing the pathogenic significance of Hsp70 in tumor stromal cells rather than tumor cells as widely presumed. Using transgenic mouse models of cancer, we found that expression of Hsp70 in host stromal cells was essential to support tumor growth. Furthermore, genetic ablation or pharmacological inhibition of Hsp70 suppressed tumor infiltration by macrophages needed to enable tumor growth. Overall, our results illustrate how Hsp70 inhibitors mediate the anti-cancer effects by targeting both tumor cells and tumor stromal cells, with implications for the broad use of these inhibitors as tools to ablate tumor-associated macrophages that enable malignant progression.